Overgearet toning - Et essay fra Salut les anciens, salut les modernes (2000) - Prigent, Christian (Passage - Tidsskrift for litteratur og kritik, 2012)
Christian Prigent: “Unbridled Fading” In his essay on contemporary poetry, Christian Prigent outlines one of his main ideas about literature. Literature’s role isn’t to talk mimetically about the world but rather to suggest the potential of different forms of language. Following this logic, Prigent considers poetry mainly as rhythm; not just any fixed pattern or regularity, but rather the individual’s desire as a corporeal experience. Thus he attaches great importance to difficult transgressive writers and illustrates the importance of transgression that is one way of approaching human experience in language. His text partly shape as a dialogue with other writers such as Jean-Marie Gleize and Philippe Beck.